Effects of different cognitive functions on unanticipated cutting motion using the Trail Making Test - Shibata, Satoshi; Takemura, Masahiro (Japanese Journal of Sports Physical Therapy, 2025)
Objective: The purpose of this study was to examine the effects of differences in cognitive function assessed the Trail Making Test (TMT) on lower limb joint angles and joint moments during unanticipated cutting motion.Methods: The subjects were 15 female college athletes, and lower limb joint angles and joint moments were measured during unanticipated cutting motion from the 30-cm high box. Cognitive function was calculated by subtracting the time required for TMT-A from TMT-B (⊿TMT), and subjects were divided into two groups, low and high groups. The maximum value of each parameter and the amount of change in joint angle within the interval during the first 30 % of the stance phase of the cutting motion were subjected to analysis. For statistical analysis, a t-test was used for inter-group comparisons, and the significant level was set at 5 %.Results: The maximum value of the knee joint valgus angle (p＝0.040) and the amount of change in the knee joint valgus angle (p＝0.020) were significantly greater in the low group, and the amount of change in the ankle joint dorsiflexion angle (p＝0.019) was significantly greater in the high group.Conclusion: Low cognitive function assessed by TMT was found to be associated with motor characteristics such as increased knee joint valgus angle.